To assess impact of organizational factors on cloud computing adoption in SMEs - Abdollahzadehgan, Azam (2013)
Cloud computing has emerged as one of the most challenging topics, discussed among enterprises of IT professionals. Multiple factors influence on cloud computing adoption, and evaluating the impact of organizational factors on cloud computing adoption in SMEs, was determined as the main purpose of this study, which leads to focusing on the TOE framework as a famous theory on the evaluation of IT adoption. Due to the mentioned purpose, organizational context divided into three main factors based on TOE framework. Three sets of critical success factor’s criteria were chosen by review of previous studies for each level of the three organizational factor’s levels. The proposed framework in this study is comprised of TOE framework, organizational factors and critical success factors criteria, which will be helpful for small and medium size enterprises which aim to evaluate their organizational condition for adopting the cloud based services. This framework has been examined empirically on 20 SMEs in Iran which apply cloud computing. Results after data analysis indicated that top management support, firm size, and technology readiness have a positive effect of adopting cloud based services in SMEs.